Testicular Adrenal Rest Tumors in Patients with Congenital Adrenal Hyperplasia: A Case Series - Didem Yildirimçakar; Selda Ayça Altincik; Murat Öcal; Bayram Özhan (Trends in Pediatrics)
Objective: Testicular adrenal rest tumors (TARTs) are the main etiology of infertility in congenital adrenal hyperplasia (CAH). The aim of this study is to determine the patients diagnosed with TART and to evaluate the risk factors associated with the development of the disease.